Quantification of DNA methylation for COMT, RELN and HTR2C in schizophrenia using methylight assay - Abd. Rahim, Nour El Huda; Rahim, Mohd Nabil Fikri; Ku Zaifah, Norsidah; Talib, Norlelawati A. (2015)
Epigenetic is an interaction between the environment and gene and has been attributed with pathogenesis of many complex diseases such as Schizophrenia (Sz) and also has been debated for future pharmacotherapeutic approach. The purpose of this study is to optimize the MethyLight assay method for quantification of DNA methylation for Catechol-O-methyltransferase (COMT), Reelin (RELN) and 5-hydroxytryptamine (serotonin) 2C receptor (HTR2C) genes and assessing 2 reference genes, (β-actin) ACTB and ALU for its use. To assess the efficiency of MethyLight assay at different percentage of DNA methylation, DNA of universal human methylated and unmethylated samples were made into serial methylation percentage and subjected to bisulfite treatment. The primers and probes of the genes were designed to cover CpG rich sites while reference genes based on suggested literature. To assess the sensitivity of the assay at different DNA concentration, the universal human methylated DNA was diluted into 1:3 serial dilutions. Both assessments were subjected to real-time PCR assay. Amplification curves for target and reference genes were plotted at acceptable Cq values. However, the assay for HTR2C, ALU and ACTB were unable to differentiate the Cq values based on the percentage of DNA methylation, whilst the amplification assay and Cq values of RELN and COMT were proportionate and able to differentiate the percentage of DNA methylation. Serial dilution of the samples showed an acceptable standard curves with R2 range from 0.80 to 1.00. In conclusion, ALU and ACTB can be used for reference genes as both assays showed no differences of Cq values against various percentage of DNA methylation. However ALU was more preferable as the dilution series showed a better assay efficiency especially at lower concentration of DNA. The assay for COMT and RELN were sensitive and specific for detection and quantification of DNA methylation.